Media Use in Virtual Teams of Varying Levels of Coordination. Issue 2 (June 2018) - Aritz, Jolanta; Walker, Robyn; Cardon, Peter W.
This study was undertaken to provide a more complete understanding of how the selection of various media in virtual team settings affects student team coordination. A total of 75 teams of 304 undergraduate participants took part in the study. Participants were asked to complete surveys before and after the project. Findings suggest that well-coordinated teams appeared to have anticipated the usefulness of social networking and richer communication channels earlier in the project than less well-coordinated teams. After engaging in virtual teamwork, team members identified rich and social channels as more effective while finding less rich channels to be less effective.